Maintenance of genome integrity by the late-acting cytoplasmic iron-sulfur assembly (CIA) complex - Petronek, M. S.; Allen, B. G. (Frontiers in Genetics, 2023)
Iron-sulfur (Fe-S) clusters are unique, redox-active co-factors ubiquitous throughout cellular metabolism. Fe-S cluster synthesis, trafficking, and coordination result from highly coordinated, evolutionarily conserved biosynthetic processes. The initial Fe-S cluster synthesis occurs within the mitochondria; however, the maturation of Fe-S clusters culminating in their ultimate insertion into appropriate cytosolic/nuclear proteins is coordinated by a late-acting cytosolic iron-sulfur assembly (CIA) complex in the cytosol. Several nuclear proteins involved in DNA replication and repair interact with the CIA complex and contain Fe-S clusters necessary for proper enzymatic activity. Moreover, it is currently hypothesized that the late-acting CIA complex regulates the maintenance of genome integrity and is an integral feature of DNA metabolism. This review describes the late-acting CIA complex and several [4Fe-4S] DNA metabolic enzymes associated with maintaining genome stability.